Controls of Fish Mercury Concentrations in Subarctic Lakes of Canada - Moslemi Aqdam, Mehdi (University of Waterloo, 2022)
Mercury (Hg) is a global pollutant that in its organic and more toxic form, methyl Hg (MeHg), can cause detrimental health effects on fish, wildlife, and humans. In lake ecosystems, concentrations of Hg ([Hg]) in fish reflect a complex outcome of interactions among variables that act at different ecological and spatial scales. From catchment and lake characteristics to fish and food web ecology, numerous processes interact to influence Hg uptake, methylation, bioaccumulation, and biomagnification, and ultimately, [Hg] in fish. As a result, fish [Hg] often vary among lakes and species, and among individuals of the same population. While factors that affect fish [Hg] in lakes are well studied and generally well understood, the relative importance and influence of these factors can vary among populations, species, ecosystems, and geographical regions, making it difficult to generalize and predict variability in fish [Hg]. Generally, little is known about controls of fish [Hg] in northern regions, where ecosystems and biota can be profoundly influenced by environmental perturbations, and where fish provide a critically important subsistence food source. In the subarctic Dehcho Region, Northwest Territories, Canada, fish [Hg] vary widely among lakes due to largely unknown mechanisms, and have, on occasion, triggered both general and site-specific consumption notices (sometimes referred to as consumption advisories or contaminant advisories). These advisories, and the lack of understanding about sources of among-lake variation in fish [Hg], are of concern for First Nation communities that rely on wild-caught fish as a subsistence food source. This thesis is aimed to address knowledge gaps regarding causes of among-lake variation in fish [Hg] in the Dehcho Region, and to improve the current understanding of what variables and processes control fish [Hg] in remote and understudied subarctic lakes. In Chapter 1, I provide a detailed overview of freshwater fish and fisheries, Hg cycling in the environment, and controls of ...